2017
DOI: 10.1093/heapol/czx127
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial support for adolescent girls in post-conflict settings: beyond a health systems approach

Abstract: Adaptive and adequately resourced health systems are necessary to achieve good health outcomes in post-conflict settings, however domains beyond the health system are also critical to ensure broader wellbeing. This paper focuses on the importance of psychosocial support services for adolescent girls in fragile contexts. Its starting point is that adolescence is a pivotal time in the life course but given the physical, cognitive and emotional changes triggered by the onset of puberty, it can also be a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 17 publications
(18 reference statements)
0
37
0
1
Order By: Relevance
“…Despite this high burden, relatively little research has unpacked this among adolescents. Notable exceptions exist and include Samuels et al ( 2017 ) who note the need to go beyond the health system to ensure broader well-being for adolescent girls in fragile contexts. The findings highlight the challenges of humanitarian and biomedical models to address such complexities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Despite this high burden, relatively little research has unpacked this among adolescents. Notable exceptions exist and include Samuels et al ( 2017 ) who note the need to go beyond the health system to ensure broader well-being for adolescent girls in fragile contexts. The findings highlight the challenges of humanitarian and biomedical models to address such complexities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Currently poverty is the main contributor of psychosocial vulnerability in adolescent girls in post-conflict settings in northeastern parts of the country (Samuels et al , 2017). In the 1990s, many men were at the war front and the government had to create employment opportunities for young women (Lynch, 2007).…”
Section: Poverty and Womenmentioning
confidence: 99%
“…Many apparel factories were established in free-trade zones and this industry has remained the country's largest net foreign exchange earner since 1992 (Dheerasinghe, 2009). Despite families valuing education, a significant number of young women dropped out from secondary education due to poverty, romantic relationships or early marriage (Samuels et al , 2017). Many in this group ended up as garment workers living away from their traditional social networks.…”
Section: Poverty and Womenmentioning
confidence: 99%
“…In Uganda, Morgan et al (2017) show how mothers reported a lack of control over financial resources and how they are used, as well as lack of male support when purchasing items for delivery or hiring transportation to the health facility. In Gaza, Samuels and Jones (2017 ) demonstrate how access to counselling following violence or trauma is mediated by gendered cultural norms. Witter et al (2017b ) demonstrate how across four different fragile contexts access to training—and especially in-service training and upgrading—was particularly difficult for women, especially when it involved travel and time away from households and gendered caring responsibilities.…”
Section: How Do the Papers Demonstrate The Value Of Gender Analysis?mentioning
confidence: 99%
“…Although not an explicit focus of any of the papers; gendered violence emerges as a clear theme. Adolescent girls experience sexualised violence in Liberia where hyper-masculinity has become the norm following years of conflict ( Samuels and Jones 2017 ); in Tanzania PMTCT processes can put women at risk of violence if they are seen as having brought HIV into the marriage ( Nyamhanga et al 2017 ); and in Uganda pregnant women experience violence from their husbands and from health workers during delivery ( Morgan et al 2017 ). Health workers themselves are also at risk of violence, particularly in times of conflict where they can be a deliberately targeted; with female health workers at increased risk of sexual violence ( Witter et al 2017b ).…”
Section: How Do the Papers Demonstrate The Value Of Gender Analysis?mentioning
confidence: 99%